Teacher Exemplary Model in Forming Akhlakul Karimah Students: Guru Teladan dalam Membentuk Siswa Berakhlak Mulia - Ubaidilah, Kholilurrohman; Haryanto, Budi (Indonesian Journal of Education Methods Development, 2025)
General Background: Moral education in Islamic schools plays a central role in shaping students’ character and social responsibility. Specific Background: In the context of SMA Assakinah Sidoarjo, the Islamic Religious Education teacher serves not only as an instructor but also as a daily role model whose behavior directly reflects religious ethics in practice. Knowledge Gap: Previous discussions often emphasize normative perspectives on moral instruction without deeply describing how exemplary conduct is implemented and observed in a specific school environment. Aims: This study aims to analyze the formation of Akhlakul Karimah among students through the teacher’s exemplary model and to describe its achievements in the school context. Results: Using a qualitative case study approach, the findings show that habituation, modeling, and advice contribute to students’ discipline, religious practices, respectful behavior, and avoidance of negative actions. Supporting factors include professional educators, school leadership motivation, and a conducive environment, while parental attention and social media exposure become constraints. Novelty: This study provides an in-depth case-based description of how exemplary practices are systematically integrated into daily school programs. Implications: The findings underline the strategic position of Islamic Religious Education teachers in embedding moral values through consistent conduct, structured religious activities, and school culture development. Keywords: Akhlakul Karima, Islamic Religious Education, Teacher Role Model, Moral Education, Character Formation Key Findings Highlights: Habituation and daily religious routines cultivate disciplined and respectful student conduct. Consistent educator behavior strengthens spiritual activities and social responsibility. School culture programs support sustained moral development despite external constraints.